Personality Traits vs. Sports Classes of Polish Representatives in Junior Sports Acrobatics - Paweł Piepiora; Adrianna Naczyńska (MDPI AG, 2023)
The aim of this paper was to determine the influence of adolescence, training discipline, and training regime on the personality formation of adolescent sports acrobats. Therefore, the purpose of this paper was to study the relationship between the personality traits and the sports classes of Polish junior sports acrobatics representatives. The respondents (N = 90) were juniors aged 18-19 and were divided into three samples: (1) n = 30 Polish representatives in sports acrobatics with a first or master sports class; (2) n = 30 kata athletes from Kyokushin karate and Shotokan karate as a reference sample from another sports discipline with gymnastic movement expression; (3) n = 30 high school students as a reference sample of non-athletic persons. The Big Five model was used, and the NEO-FFI personality questionnaire was used as a research tool. For the analyses of basic descriptive statistics, the Kruskal-Wallis test and Mann-Whitney test were performed to determine statistical significance (α = 0.05). It was noted that all athletes (the first and second samples) had personality traits at the same levels: low neuroticism, high extraversion, moderate openness to experience and agreeableness, and high conscientiousness in relation to non-athletes. In contrast, there were differences among the subjects in personality traits, except for agreeableness. Among the sports acrobats, master-class athletes showed lower neuroticism, greater openness to experience, lower agreeableness, and greater conscientiousness in relation to first-class athletes. It was found that there were differences between the personality traits and sports classes of junior sports acrobatics representatives in Poland in the four Big Five dimensions. But in general, sports acrobats and karate athletes had personality traits at similar levels, and at the same time, different from non-training people.